2012
DOI: 10.1902/jop.2011.110016
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Implants Immediately Placed in Sites With and Without Periapical Pathology in Sixty‐Four Patients

Abstract: Implants immediately placed in sites demonstrating periapical pathology yielded results comparable to those immediately placed in pristine sites. The difference in survival rates was not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 11 publications
4
69
0
3
Order By: Relevance
“…The result reflects and confirms the hypothesis that endosteal implants can be successfully integrated in infected sites. However, alveolar ridge resorption after the tooth extraction is a frequent occurrence and may significantly reduce the residual bone volume [23][24][25][26][27][28]. This study is a proof of principle that sockets can heal naturally with immediately placed implants in infected sites and tissue shrinkage can be reduced by utilizing least invasive surgical and prosthetic protocol.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The result reflects and confirms the hypothesis that endosteal implants can be successfully integrated in infected sites. However, alveolar ridge resorption after the tooth extraction is a frequent occurrence and may significantly reduce the residual bone volume [23][24][25][26][27][28]. This study is a proof of principle that sockets can heal naturally with immediately placed implants in infected sites and tissue shrinkage can be reduced by utilizing least invasive surgical and prosthetic protocol.…”
Section: Introductionmentioning
confidence: 77%
“…Since then, this treatment modality has received much attention in the literature [13] Fugazzotto [25] conducted the only study comparing implants immediately placed into sites with periapical pathology with those immediately placed into sites without periapical pathology in the same patient, thus helping to control a number of interpatient variables and render the results more directly clinically applicable. It was observed that both treatments yielded comparable results with no statistically significant difference in survival rates.…”
Section: Introductionmentioning
confidence: 99%
“…The bone destruction pattern resulting from periapical pathology should be taken into account when considering immediate placement. Fugazzoto (9) suggests a classification system for periapical lesions: 1 to 3, depending on bone availability to ensure primary stability and to guide clinical procedures.…”
Section: Workhop 1 -Ideal Time For Implant Placement: Immediate Earmentioning
confidence: 99%
“…El patrón de destrucción ósea como resultado de la presencia de patología periapical debe examinarse al considerar el tiempo de inserción inmediato. Fugazzoto (9) propone un sistema de clasificación de la lesión periapical, tipificándola del 1 al 3 en función de la disponibilidad ósea que asegure la estabilidad primaria, orientando la conducta clínica a seguir. Tipo 1: Existe suficiente hueso periapical para lograr estabilidad primaria Tipo 2: No existe adecuado remanente periapical para asegurar estabilidad primaria, esta se logra lateralmente.…”
Section: Introductionunclassified
“…Twelve of the articles were excluded as they had no IOPAs of the lesion. 7,11,24,25,33,35,[37][38][39]45,48,53 A total of 54 IOPAs from 36 articles were compiled. One periodontist (SR) and one implantologist (TAB) independently analyzed the IOPAs.…”
Section: Literature Searchmentioning
confidence: 99%